Expression, partial characterisation and utilization of a GH11 xylanase (Xyn2A) from Trichoderma viride as an additive in monogastric animal feeds - Mzimkulu-Ncoyi, Nosabatha Happyness (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Endo-xylanases (shortly called xylanases) are a group of glycoside hydrolase enzymes that target Î²-D-1,4-linkages in the xylan backbone, leading to the production of xylooligosaccharides (XOS) of varying degree of polymerization (DP). Xylan is an indigestible non-starch polysaccharide present in monogastric animal feeds which in high amounts leads to increased digesta viscosity, slow movement of digesta in the intestines, malabsorption of nutrients among other challenges. The aim of this study was to investigate the effect of xylanase 2A (Xyn2A) from Trichoderma viride on broiler chicken feeds, particularly the hydrolysis of the xylan content, reduction of feed viscosity and the effect of produced XOS on eliciting the growth of gut associated probiotic bacteria. Xyn2AE was successfully induced with 0.8 mM isopropyl Î²-D-1-thiogalactopyranoside (IPTG) and produced in Escherichia coli BL21 (DE3) and Xyn2AC was expressed in tobacco mosaic plants. For the purification of Xyn2AE, an immobilized metal affinity chromatography (IMAC) column and diafiltration using a 3kDa cut-off Amicon filter membranes were used. Xyn2AE and Xyn2AC showed a xylanase active band at a relative weight of 21 kDa. Both enzymes showed high specificity towards soluble wheat arabinoxylan (WAX), with specific activities of 7.61 U/mg for Xyn2AE and 536.5 U/mg for Xyn2AC. Xyn2A kinetic parameters (Vmax and Km) were determined by Michaelis-Menten plots on soluble and insoluble WAX. The Vmax and Km values of Xyn2AC were 1003.01 U/mg and 9.25 mg/mL, 302.89 U/mg and 13.54 mg/mL, respectively. The Vmax and Km values of Xyn2AE for soluble and insoluble WAX were 20.45 U/mg and 12.95 mg/mL, and 8.31 U/mg and 13.15 mg/mL. Xyn2A enzymes displayed optimum activity at pH and temperature parameters of 5.0 and 50Â°C, respectively, and stability in temperatures ranging between 50 and 80Â°C and pH 4.0-9.0. Broiler chicken feeds were hydrolysed using Xyn2AE over a 24 h period and analysed using the dinitrosalicylic (DNS) assay, thin layer chromatography (TLC), viscometry and visualized using scanning electron microscope (SEM). The results showed a release of release of XOS xylotriose, xylopentose and xylohexose; enzyme's ability to decrease the viscosity of the feeds and punched holes of feed surface, which was indicative of xylanase action. XOS produced during hydrolysis was used to study prebiotic effect on selected few bacteria and released short chain fatty acids (SCFAs) were measured. Additionally, SCFAs formation was detected in the presence of XOS as a carbon source for S. thermophilus and L. bulgaricus, whereas B. subtilis formed fewer organic acids in the presence of XOS. The results obtained from this study demonstrated that the supplementation of Xyn2A on broiler feeds has ii a positive effect in decreasing feed viscosity. Furthermore, the results of this investigation will assist the South African poultry farming sector to increase profitability in poultry farming and gain stability in the global trade as far as poultry feed is concerned.
Keywords: Feed additives; Xylanases; Trichoderma viride; Monogastric; Polysaccharides; Plant cell walls; Prebiotics